2015
DOI: 10.1016/j.neuroscience.2015.03.035
|View full text |Cite
|
Sign up to set email alerts
|

The neural bases of the pseudohomophone effect: Phonological constraints on lexico-semantic access in reading

Abstract: We investigated phonological processing in normal readers to answer the question to what extent phonological recoding is active during silent reading and if or how it guides lexico-semantic access. We addressed this issue by looking at pseudohomophone and baseword frequency effects in lexical decisions with event-related functional magnetic resonance imaging (fMRI). The results revealed greater activation in response to pseudohomophones than for well-controlled pseudowords in the left inferior/superior frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 98 publications
(173 reference statements)
1
23
0
3
Order By: Relevance
“…While the pseudohomophone effects reported in this study were only found in the errors rates, and not in the reaction time analysis, this is not such an uncommon finding. It should be considered that the stimuli used this experiment were relatively short (4-6 letters) and based on high frequency words, and some preceding studies have also failed at finding significant pseudohomophone effects for highfrequency items (e.g., Braun et al, 2015), and others have exclusively found the effects in the error data (e.g., Briesemeister et al, 2009). Importantly, for deaf skilled readers error percentages were similar for pseudohomophones and control nonwords, suggesting that they did not activate phonological codes.…”
Section: Discussionmentioning
confidence: 99%
“…While the pseudohomophone effects reported in this study were only found in the errors rates, and not in the reaction time analysis, this is not such an uncommon finding. It should be considered that the stimuli used this experiment were relatively short (4-6 letters) and based on high frequency words, and some preceding studies have also failed at finding significant pseudohomophone effects for highfrequency items (e.g., Braun et al, 2015), and others have exclusively found the effects in the error data (e.g., Briesemeister et al, 2009). Importantly, for deaf skilled readers error percentages were similar for pseudohomophones and control nonwords, suggesting that they did not activate phonological codes.…”
Section: Discussionmentioning
confidence: 99%
“…The core ideas of these studies is that, if the homophone of a word is incorrectly accepted as member of the target word category, then this means that phonology is involved in word recognition and comprehension (homophony effect). A large homophone effect was observed for words (Van Orden, 1987;Braun, Hutzler, Münte, Rotte, Dambacher, Richlan & Jacobs 2015) and nonwords (Van Orden et al, 1988;Braun et al, 2015), suggesting that not only phonological coding is rapid but also automatically activated (along with orthographic information) and used for accessing word meaning. Although replicated with other tasks (e.g., masked priming in silent reading, Perfetti, Bell, & Delaney, 1988), the homophone effect was found to be significantly sensitive to list composition (Brysbaert, Praet, & d'Ydewalle, 1990) and lexical frequency (Jared & Seidenberg, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…While visual and orthographic processes are mainly associated with left posterior inferior occipital as well as left ventral occipitotemporal activations, phonological and semantic processes additionally recruit higher-order language areas, such as left temporal and left inferior frontal regions (e.g., Poldrack et al, 1999; Dehaene et al, 2002; Kronbichler et al, 2007; Welcome and Joanisse, 2012; Schurz et al, 2014; Braun et al, 2015; Cavalli et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Thornton and Light, 2006; Burke and Shafto, 2008). When it comes to age-related effects on phonological processing in visual word recognition, however, there is an apparent lack of research, although it is known that phonological representations are automatically activated during silent reading even in highly skilled readers (e.g., Ziegler and Jacobs, 1995; Braun et al, 2009, 2015; Briesemeister et al, 2009). The phonological decision task, which forces participants to engage in phonological rather than in orthographic processing during silent reading, is therefore exceptionally well suited for our purposes and has not yet been administered to an older cohort (Kronbichler et al, 2007; Bergmann and Wimmer, 2008).…”
Section: Introductionmentioning
confidence: 99%